2018
DOI: 10.1371/journal.pgen.1007227
|View full text |Cite
|
Sign up to set email alerts
|

Dek overexpression in murine epithelia increases overt esophageal squamous cell carcinoma incidence

Abstract: Esophageal cancer occurs as either squamous cell carcinoma (ESCC) or adenocarcinoma. ESCCs comprise almost 90% of cases worldwide, and recur with a less than 15% five-year survival rate despite available treatments. The identification of new ESCC drivers and therapeutic targets is critical for improving outcomes. Here we report that expression of the human DEK oncogene is strongly upregulated in esophageal SCC based on data in the cancer genome atlas (TCGA). DEK is a chromatin-associated protein with important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 81 publications
0
16
0
Order By: Relevance
“…DEK protein expression was higher in OSCC tissues than in the normal tissues, and the percentage of positive cells was > 50% in almost all samples (30/34 cases) [19]. These Recently, two DEK-overexpressing murine models have been reported [19,45]. Matrka et al [45] established a tetracycline-inducible DEK transgenic mouse model to investigate whether DEK contributes to carcinogenesis in vivo.…”
Section: Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%
See 3 more Smart Citations
“…DEK protein expression was higher in OSCC tissues than in the normal tissues, and the percentage of positive cells was > 50% in almost all samples (30/34 cases) [19]. These Recently, two DEK-overexpressing murine models have been reported [19,45]. Matrka et al [45] established a tetracycline-inducible DEK transgenic mouse model to investigate whether DEK contributes to carcinogenesis in vivo.…”
Section: Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%
“…These Recently, two DEK-overexpressing murine models have been reported [19,45]. Matrka et al [45] established a tetracycline-inducible DEK transgenic mouse model to investigate whether DEK contributes to carcinogenesis in vivo.…”
Section: Squamous Cell Carcinoma Of the Head And Neckmentioning
confidence: 99%
See 2 more Smart Citations
“…DEK is a chromatin remodeling protein whose overexpression has been reported to reprogram cellular metabolism, stimulate cell proliferation, increase invasion and metastasis, etc [20][21][22]. In addition, high DEK expression is an independent prognostic factor associated with aggressive disease and poor outcome in solid tumors, including breast cancer [23][24][25]. The ORI results we acquired demonstrated that MDA-MB-231 cells with decreased DEK expression (DEKsh) had a significantly lower FAD redox ratio than the vector treated control cells (NTsh).…”
Section: Introductionmentioning
confidence: 99%